Pengaruh Pencahayaan dan Penghawaan Alami pada Bangunan Sekolah Terhadap Keluhan Sick Building Syndrome bagi Pelajar - Wasiela, Nurul; Subiyantoro, Heru (Universitas Medan Area, 2025)
Students in Indonesia currently spend up to 8 hours a day in the school environment to attend teaching and learning activities. This time is certainly not a short time especially since most of the activities are carried out in the classroom. This of course can cause boredom and even complaints of Sick Building Syndrome. Some of the causes of Sick Building Syndrome (SBS) are due to the poor quality of lighting and natural ventilation in the building and have not met the requirements of healthy air. School is one of the buildings that need to be considered in a design, especially classrooms for the learning comfort of students who spend most of their time at school. This research uses descriptive-quantitative method by collecting data in the form of observation through observation and distribution of questionnaires and architectural literature used from related sources. The object of this research is SMP Negeri 1 Cilacap School, starting with identifying the characteristics of the subject and the symptoms of Sick Building Syndrome and continuing with the test of the environmental conditions of the learning place by analyzing the size of the room, building orientation, temperature, humidity, wind speed related to natural lighting and ventilation to create a comfortable and adequate learning space for learning. The results showed that the variables of room size, temperature and wind speed were in accordance with the subject data while building orientation and humidity were not in line with the test results of the subjects of each class.